Guiding role of the teacher in general middle education - Morillo Gutiérrez , Maricarla Nazareth; Araujo Ferrer , Felipe Rafael; Pérez Vides , Darnellis Carolina; Valenzuela , Luz (Frónesis, 2019)
The main purpose of this article is to socialize the results obtained from an investigation aimed at describing the tasks performed by teachers from their guiding role in General Secondary Education, specifically in the U.E. Valerio Toledo. The teacher of any level is trained to carry out not only the role of mediator, but also of guidance, in which he will help the student to know and understand himself, discover his potentialities, overcome his limitations, go to his personal development and optimal social adaptation and encourage them in vocational decision-making, contributing to their psycho-affective consolidation. This research was characterized by belonging to the positivist epistemological approach. A structured questionnaire with a Likert scale was designed and applied in order to obtain information regarding the research to a sample that was represented by the entire population, distributed as follows: fifteen (15) teachers and seventy (70) 1st-year General Secondary Education students From the results obtained, it was concluded that teachers in their guiding role perform tasks such as: personalized attention to students who require help in particular situations, referral of students, who deserve it, to the services of the coordination of protection and integral health, stimulation of the personal growth of the students through special activities in support of the orientation services of the campus, among others